Epidemiologica and factors risk of stroke in Kemerovo - A. V. Kovalenko; O. A. Gileva (Бюллетень сибирской медицины, 2008)
The paper presents the results of the first prospective epidemiological study of stroke in Kemerovo. The stroke was primary in 77,1% patients, the second one was in 22,9% patients. The frequency of the development of stroke increased with the years. The most prevalent risk factor was arterial hypertension which was recorded in 91,6% patients. Cardiac pathology as a stroke risk factor ranked second (61,7%). Cerebrovascular disorders in close relatives were registered in 55,5% patients. One-month lethality was 41,1%.